The role of the Arabic language semantics in legal drafting and achieving justice (The International Journal for Scientific Research, 2024)
The linguistic construction of legal texts is one of the most important aspects in achieving precision in the fair application of legal provisions in all countries without exception. The meaning of a word within the context of its structure, and the relationships between structures, are fundamental to achieving an accurate semantic construction within the precise drafting of legal provisions in a way that ensures their application realizes justice.This research addresses the role of the Arabic language and semantics in constructing legal formulations in a precise manner that cannot be compromised, thereby ensuring the establishment of rights and the realization of justice among members of society through a correct understanding of the language of these legal provisions. This is done by examining the field of semantics, the emergence of this science, the construction of legal formulas in Iraqi law, and the impact of this construction on the correct understanding of legal provisions and its effect on the validity of their application, ensuring the achievement of justice.
Keywords: Law; Language; Drafting; Semantics; Structure